Expanding the European dimension in energy policy: the Commission’s latest initiatives - Buchan, D (Oxford Institute for Energy Studies, 2011)
The European Commission has broken new ground in proposing to streamline national planning approval of vital energy infrastructure, use EU funds to leverage private finance for such networks and to negotiate foreign pipelines on the EU’s behalf. These initiatives coincide awkwardly with the eurozone crisis. But David Buchan broadly endorses Brussels’ attempt to kick-start implementation of Europe’s 2020 energy and climate goals. He suggests the Commission go a step further by taking advantage of the forthcoming treaty revision to propose a constitutional amendment on EU states’ energy mix.